2022
DOI: 10.1002/1873-3468.14339
|View full text |Cite
|
Sign up to set email alerts
|

Interaction kinetics reveal distinct properties of conformational ensembles of three‐repeat and four‐repeat tau proteins

Abstract: Tau protein is an intrinsically disordered protein. Its physiological state is best described as a conformational ensemble (CE) of metastable structures interconverting on the local and molecular scale. The monoclonal antibody DC39C recognizes a linear C‐terminal tau epitope, and as the tau interaction partner, its binding parameters report about tau CE. Association kinetics of DC39C binding, together with crosslinking mass spectrometry, show differences in the accessibility of the C terminus in CEs of tau iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Such an existence of the helix structure at the Cterminus is reasonable because NMR experiments supported the preference for alpha-helical structure at this region. 58,62,63 Mukrasch et al observed the preference for α-helical structure at residues 428−437 for 25% of time. The over stability of the helix structure for the hydrophobic C-terminal segment in our simulations compared to Mukrasch's study may due to the limitation of adopted force fields, but it is of note that other experimental and theoretical studies support the stable helix structure of the same segment.…”
Section: Radius Of Gyration From Typical Cg-md Snapshots Agrees With ...mentioning
confidence: 99%
“…Such an existence of the helix structure at the Cterminus is reasonable because NMR experiments supported the preference for alpha-helical structure at this region. 58,62,63 Mukrasch et al observed the preference for α-helical structure at residues 428−437 for 25% of time. The over stability of the helix structure for the hydrophobic C-terminal segment in our simulations compared to Mukrasch's study may due to the limitation of adopted force fields, but it is of note that other experimental and theoretical studies support the stable helix structure of the same segment.…”
Section: Radius Of Gyration From Typical Cg-md Snapshots Agrees With ...mentioning
confidence: 99%